A practical approach to weight loss in adult horses. (2nd March 2023) - Corradini, Ignacio
Abstract : Common causes of weight loss in horses include inadequate dietary intake, dental problems and endoparasites. However, once these common causes are ruled out, the spectrum of weight loss causes can be ample and in some cases, may indicate the presence of severe illness. Given the clinical relevance of weight loss, the equine clinician is faced with important questions that need to be answered. A systematic diagnostic approach to weight loss should be followed.